Literasi Digital dalam Meningkatkan Kesadaran Siswa terhadap Bahaya Child Grooming di Era Digital - Adinda Dwi Cahyani; Ully Arta Silitonga; Risma Anita Puriani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Digital literacy is an individual's ability to access, understand, evaluate, and use digital information and technology wisely, critically, and responsibly. This skill is crucial for students to use technology safely and avoid various risks in the digital space. The development of digital technology and the increasingly widespread use of social media have provided various conveniences in people's lives, particularly in communication and information access. However, on the other hand, these developments also pose various risks for children and adolescents, one of which is the crime of child grooming in the digital space. Child grooming is a manipulative act perpetrated by adults by building emotional closeness and trust with children for the purpose of sexual exploitation. This study aims to examine the role of digital literacy in raising students' awareness of the dangers of child grooming in the digital era. The method used in this study was a Systematic Literature Review (SLR. The results indicate that low digital literacy among students makes them more vulnerable to various forms of digital crime, including child grooming that occurs through social media and online games. Conversely, strengthening digital literacy through education in schools, the role of guidance and counseling teachers, and parental supervision can increase students' awareness of the risks of digital interactions and protect themselves from potential cybercrimes. Therefore, digital literacy is a crucial effort in preventing child grooming and protecting children in the era of information technology development.